Case Study Community Archaeology Approach in the Management of Cultural Heritage on the Slopes of Mount Merbabu: A Case Study of the Ngadirojo Archaeological Site: Pendekatan Arkeologi Komunitas dalam pengelolaan Warisan Budaya Lereng Gunung Merbabu: Studi kasus Situs Arkeologi Ngadirojo, Boyolali, Indonesia - Nurul Fadilla Budiana; Dede Aditya (Berkala Arkeologi, 2026)
Research on the ancient spiritual landscape of Mount Merbabu has received limited scholarly attention. Recent discoveries in Margomulyo (Timboa), Ngadirojo, Boyolali Regency reveal unique findings, including the surface remains of talud structures, ancient stairways, and inscription located below Prego Dalem Peak. The Mount Merbabu National Park Authority (BTN Gunung Merbabu) is responsible for securing the Ngadirojo Archaeological Site, placing within the park’s Core Zone. This condition raises an important question: How effective is the current restricted conservation policy for the site? This study aims to propose a community-based archaeological heritage management approach for its preservation. Data collection was conducted through desk research and interviews with Margomulyo (Timboa) residents. The results highlight the community’s potential and its surroundings as a supporting area for developing the Mount Merbabu Cultural Center, offering a viable solution for the conservation of the Ngadirojo Archaeological Site.